Lexical Patterns and Their Semantic Implications in Surah-Al-Hujrat: A Corpus-Based Approach (Journal of Asian Development Studies, 2025)
This research aims to investigate the complicated lexical patterns and their semantic consequences in Surah Al-Hujurat. To achieve this, a corpus-driven analytical framework is utilized to unveil the profound linguistic and thematic structures that are the foundation of this chapter of the Quran. This research intends to highlight the chapter's overriding emphasis on societal peace, ethical conduct, and divine direction by examining the semantic richness and syntactic complexity of important lexemes. Such an analysis will be carried out to accomplish this. The study analyses the Surah's rhetorical impact and thematic coherence by looking for specific lexical patterns in collocations, concordances, and frequency distributions. For instance, the recurrent utilization of phrases that are related to “brotherhood" (ةوذ), "obedience" ( ط ﺔﻋﺎ ), and "rectification" ( ﻼﺻ إ ح ) demonstrates a complex interaction between the responsibilities of individuals and the welfare of the community. Research places these results in the context of the Quran's language and shows how the vocabulary of Surah Al-Hujurat teaches a new way of thinking about ethics and how to follow God's commands. This work unites modern linguistic analysis with classical Quranic exegesis by using cutting-edge corpus techniques and methodology; as a result, it sheds new light on the textual complexity and intended meaning of Surah Al-Hujurat. This extensive analysis highlights the literary richness of the Quran by illuminating the connections between the lexical patterns and the social, spiritual, and moral aspects of the text.